Assessment of Risk Profile on LPD in East Denpasar District - I M Sarjana; I M A Anggara (Journal of Applied Sciences in Accounting, Finance, and Tax, 2020)
Lembaga Perkreditan Desa--Village Credit Institutions (LPD), located in almost all indigenous villages in Bali, are financial institutions in which all their activities use funds from traditional village communities. Therefore the level of business health needs to be considered well. LPD will be able to achieve a healthy predicate if the managers are able to work well based on good goals and free from risk. In this regard, it is important to do LPD assessment relating to the risk profile. This study aims to assess the risk profile in terms of credit, liquidity, operational and capital risk factors on the LPDs in East Denpasar District 2016-2018. The types of data in this study is qualitative and quantitative, while data sources are secondary. The procedure for data collection is done by documentation. The results of the study obtained an assessment of risk profile 2015-2017 in terms of credit risk factors in the ratio of earning asset quality and the allowance for removal of earning assets with a very low risk rating. Risk profile assessment is viewed from liquidity risk factors in the liquidity index ratio with a very high risk rating. Risk profile assessment in terms of operational risk factors in the effectiveness ratio with a risk rating is very high and the efficiency ratio with a risk rating is very low. Risk profile assessments in terms of capital risk factors at a minimum capital adequacy ratio are very low. The overall risk profile assessment shows the risk rating is low.